THE USE OF SHOW AND TELL (S&T) STRATEGY IN TEACHING VOCABULARY FOR THE KINDERGARTEN TEACHERS - Aini, Rizka Marlisa; Fadhilah, Nurul; Amalina, Zahria; Fahmi, Said Miftahul; Andika, Wiwi (Jurnal Buah Hati, 2024)
This study focuses on enhancing the vocabulary mastery skills of kindergarten teachers by employing the Show and Tell (S&T) method. The research adopts a quantitative approach, specifically utilizing experimental research design. A total of 12 kindergarten teachers from TK Khalifah 3 Banda Aceh participated in this study. Data collection was conducted through pre-tests and post-tests, using multiple-choice questions designed to assess vocabulary mastery. The instruments measured specific indicators, including mastery of standard language, completion of gap sentences, identification of synonyms, and recognition of antonyms. The collected data were analyzed using the T-test formula to determine the effectiveness of the intervention. The findings reveal that the implementation of the Show and Tell (S&T) strategy significantly improved the vocabulary mastery of the teachers involved. This improvement is attributed to the interactive and engaging nature of the S&T method, which encourages teachers to participate actively and develop their language skills in a more meaningful and practical manner. The study concludes that the Show and Tell (S&T) strategy is an effective tool for enhancing vocabulary skills among kindergarten teachers, equipping them with the linguistic proficiency necessary for their teaching roles. This research highlights the importance of innovative teaching methods in professional development and underscores the potential of active learning strategies in improving language skills among educators. Further studies are recommended to explore the long-term impact of the S&T method and its applicability across different educational contexts.